Aplikasi Algoritma Hybrid dalam Penentuan Rute Pendistribusian Produk (Studi Kasus: PT. Enseval Putera Megatrading) - Eri Wirdianto; Dhina Regenie; Wisnel (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
PT. Enseval Putera Megatrading is a company which operates in general business and distribution of pharmacy products, general needs, cosmetics, foods and hospital equipment. In their current practice, routing in products deliveries, which is limited by time windows, has not considered the utilization of vehicles' maximum loading capacities. Distribution route from a hybrid algorithm using heuristic clustering and Mixed-Integer Linear Programming approach can accommodate such problem with time windows and vehicles' capacities utilization. Based on the comparison between company’s current route and the route from the hybrid algorithm, it can be seen that the hybrid algorithm is able to decrease total distance and total cost of transportation. This new route concerns on vehicles allocation and time windows limit. This new route can minimize the total cost of transportation that company has to pay.